Differentially expressed genes in human gingival fibroblasts cultured on microgrooved titanium substrata: A pilot study - Lee, Suk Won (Tissue Eng Regen Med, 2012)
The purpose of this study was to determine the differentially expressed genes in human gingival fibroblasts (HGFs) cultured on titanium (Ti) substrata with topographies presenting microgrooves and acid-etched roughness. Microgrooves were fabricated with a truncated V-shape in cross-section at 15/3.5, 30/10, and 60/10 μm (width/depth) by photolithography. Subsequent acid etching was applied to the entire surface of the fabricated Ti substratum to generate etched microgrooves and ridges (designated as E15/3.5, E30/10, and E60/10). Both smooth and acidetched-only Ti were used as controls (designated as NE0 and E0). Large-scale gene expression analyses were performed using differential display PCR, and the results were confirmed using RT-PCR and quantitative real-time PCR. Of the 21 genes with altered expression determined by differential display PCR and sequencing, we verified through RT-PCR that MTDH and TIMP1 were up-regulated and TGF-β1, TPM1, and VIM were down-regulated in the HGFs cultured on E60/10 versus NE0. We also confirmed, by quantitative real-time PCR, that MTDH and TIMP1 expression in HGFs on E60/10 was significantly up-regulated compared to HGFs on the other Ti substrata. This study indicates that acid-etched ridges and microgrooves on Ti with a width and depth of 60 and 10 μm (E60/10) induce alterations in the expression of genes involved in cell adhesion, proliferation, and regulation of the cytoskeleton in HGFs.